Mutual Fund Performance and Managerial Strategies: Evidence from India - Singh, Rupy (2007)
Mutual fund industry is an upcoming market, both in terms of size and variety, especially in case of the emerging economies of the world. However, market research on both the performance and the investment strategies of the funds, hardly exist. My research, being conducted on the Indian mutual fund industry, intends to fill this gap. In my analysis, three aspects are addressed. First, does any equity fund; both growth and income out perform the market benchmark (BSE Sensex)? Second, do the fund managers have effective timings and selectivity abilities? Third, what are the most preferred investment strategies implemented by the equity fund managers? The answers from my research are: by using the risk adjusted performance measure given by Sharpe, Treynor and Jenses alpha, on average growth funds in contrast to the income funds, under the sample study, tend to under perform the market index. Treynor Mazuy model demonstrated that the fund managers did not exhibited sufficient abilities to identify the under priced securities in the market. Thus, reflected negative timing and selectivity abilities. And lastly, a qualitative survey conducted on the equity fund managers reflected that majority of the fund managers are male, hold an MBA degree and also, indicate that 'rebalancing of the portfolios in the light of the changing economic conditions' is one of their most successful strategies implemented in the emerging Indian industry.